A comparison of different particle size analysis techniques - A L Baldridge; T L Stainbrook; J C Woodworth; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2001)
In this study, we compared different methods of testing particle size of ground corn. Forty-four corn samples were analyzed for particle size with a Ro-Tap tester equipped with a 13-sieve stack (53 to 3,350 :m tyler mesh screens). Mean particle size of the 44 samples ranged from 422 to 1,143 :m. These samples were then analyzed by placing 280 g on a #14 sieve (1,400 :m). The sieve was shaken by hand as the manufacturer recommended (one-sieve method). In a second procedure, samples were analyzed by placing 50 g of corn on a stack of three sieves: US #12 (1700 :m), #30 (600 :m), and #50 (300 :m: three-sieve method) with balls and carnucles. The three-sieve method was much more reliable in predicting average particle size of ground corn than the one-sieve method when compared to the 13- stack standard operating procedure. In summary, the three-sieve procedure may be a more accurate method to quickly determine particle size than the one-sieve method.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Ground corn; Particle size; Procedures